2018
DOI: 10.1007/s13744-018-0651-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-lethal Doses of Imidacloprid on Learning and Memory Formation of Indigenous Arabian Bee (Apis mellifera jemenitica Ruttner) Adult Foragers

Abstract: The indigenous bee race Apis mellifera jemenitica Ruttner of Saudi Arabia can learn and retain memories established by the classical conditioning of proboscis extension response (PER). The insecticide imidacloprid has shown a drastic effect on the olfactory behavior of A. m. jemenitica in the harsh arid climatic conditions of central Saudi Arabia. The oral feeding of single imidacloprid sub-lethal doses (1.0 ng, 0.5 ng, or 0.1 ng) under laboratory conditions significantly impaired associative learning during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
1
13
0
1
Order By: Relevance
“…These honey bees are vulnerable to many environmental threats that may affect their physiology, performance, biology, and behavior. A range of environmental stresses, such as weather, pollutants, diseases, pollen quality and diversity, nutrition deficiency, and indiscriminate use of pesticides, are linked to sudden colony collapse disorder (CCD) of honey bees (Iqbal and Mueller, 2007, Iqbal, 2009, Klein et al, 2017, Iqbal et al, 2019b). This sudden population decline has aroused concerns of an emerging pollination crisis (Holden, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These honey bees are vulnerable to many environmental threats that may affect their physiology, performance, biology, and behavior. A range of environmental stresses, such as weather, pollutants, diseases, pollen quality and diversity, nutrition deficiency, and indiscriminate use of pesticides, are linked to sudden colony collapse disorder (CCD) of honey bees (Iqbal and Mueller, 2007, Iqbal, 2009, Klein et al, 2017, Iqbal et al, 2019b). This sudden population decline has aroused concerns of an emerging pollination crisis (Holden, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhang & Nieh (2015) observed that after four days of exposure to 1.5 µg/bee of imidacloprid, short-term learning ability was reduced by 87% and memory retention was reduced by 85%. Even lower concentrations of imidacloprid (0.1 ng/bee) in the Arabic subspecies A. m. jemenitica significantly impaired learning ability and memory (Iqbal et al, 2019).…”
Section: Imidaclopridmentioning
confidence: 92%
“…This study is one element of a major research project investigating how subtropical weather conditions reflect on different key points related to bee colony performance, e.g., nectar secretion dynamics, flowering phenology, pollination ecology, the honey potential of major bee plants [20,21,25,26], the antimicrobial potential of honeys [17], associative learning and heat shock protein expression [27,28], insecticidal-induced changes in the learning of honeybees [29], and the use of geographic information systems (GIS) and remote sensing technologies to determine the optimal forage capacity [30]. The present experiment was conducted to evaluate the rates of outgoing and pollen-gathering foragers during a period of rich nectar flow.…”
Section: Introductionmentioning
confidence: 99%